Penggunaan Removable Partial Denture dengan PMMA pada Anak Post-Labiopalatoplasty - Mustika Pramidi; Yetty Herdiyati (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2015)
Children with abnormal cleft lips and palate usually suffer from dento-skeletal disorder. Since childhood, they struggle to undergo the palate corrective surgery (palatoplasty) so that nutrition can be provided at its maximum. Dental disorders, like caries, starts to show when the teeth begins to erupt. The loss of the deciduous teeth prematurely can lead to the loss of distance within the jaw arch, “tipping”, over crowding and an impact on the tooth replacement. Removable Partial Denture RPD (removable denture) on kids happens to be one of the tools that are used to maintain space due to premature loss of deciduous teeth and agenesis. During the 1940s, 95% of the bas materials for dentures are made of acrylic resin; it is popular to this day. Acrylic is more known as a polymetil metakrilat of PMMA and still happens to be a material choice when making removable dentures. to restore the function of chewing and to explain the advantages of the use of RPD with a PMMA material. Am 8 year old boy with a history of postlabiopalatoplasty came to the Clinic Pediatric Dentistry, Dental Hospital University of Padjadjaran with a complain from loss of his lower left molar and wants to be examined. An RPD case management by making unilateral on the lower left region. RPD with PMMA material has a few advantages; easy manufacturing process, a decent aesthetic, economical, easily repaired and have simple equipment.